Estimating the population of youth drug users during the COVID-19 pandemic - Abdul Ghani, Mohamad Salleh; Ramadah, Ravi; Mohd Sakri, Mohd Syazrin; Mohd@Maasom, Hafidah; Che Berahim, Siti Badariah Ismi; Hashim, Mohd Nazri; Binti Azmi, Noor Amirah Hidayah; Zainol, Intan Suraya (Human Resource Management Academic Research Society, 2023)
The COVID-19 has caused many treatment facilities to close down or not operational. This has led to a decrease in the number of drug users detected which causes the population to be underreported. For policies and strategies to be implemented effectively, an accurate estimation of the population is required. This study aims to estimate the population of youth drug users in Malaysia using an indirect method of the benchmark-multiplier method. Data from the NADAs database was used as a benchmark, and secondary data from a prevalence study was used as a multiplier. The results estimated around 654,000 individuals between the ages of 15 and 39 used drugs in 2021. This is a prevalence rate between four to five drug users for every 100 individuals within the age group. The apparent decline in the NADA yearly report could be attributed to most of the drug users being undetected primarily due to the countrys focus on the pandemic. Efforts on the issue of substance use should be increased based on the reflected number from this study. The estimates can be useful for future researchers to expand further work in estimating the population of drug users or other hidden populations.